2015
DOI: 10.1007/s10750-015-2451-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of pycnocline and dissolved oxygen on vertical distribution of moon jellyfish Aurelia aurita s.l.: a case study of Mikawa Bay, Japan

Abstract: Blooms of moon jellyfish Aurelia aurita s.l. occur in various vertical distribution patterns within the water column. Reasons for these distribution patterns have remained obscure. To quantify the influence of pycnocline and low dissolved oxygen (DO) on the vertical distribution of A. aurita aggregations, we investigated temperature, salinity, DO, and observed densities of A. aurita at 1-2 m depth intervals via video camera in a eutrophicated, enclosed bay, Mikawa Bay, Japan, for 3 years. During the observed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In the bottom layer, where A . coerulea usually aggregates in Japanese coastal waters [6163], water temperatures of 19.8–22.0°C and 17.1–21.1°C were observed in June and November, respectively (Fig 3). As the water temperature was different between the direct-development and metagenetic periods and showed similar values (approximately 20°C) in the switching periods, a water temperature of 20°C is suggested to be the threshold for switching the egg size and ontogenetic development of A .…”
Section: Discussionmentioning
confidence: 99%
“…In the bottom layer, where A . coerulea usually aggregates in Japanese coastal waters [6163], water temperatures of 19.8–22.0°C and 17.1–21.1°C were observed in June and November, respectively (Fig 3). As the water temperature was different between the direct-development and metagenetic periods and showed similar values (approximately 20°C) in the switching periods, a water temperature of 20°C is suggested to be the threshold for switching the egg size and ontogenetic development of A .…”
Section: Discussionmentioning
confidence: 99%
“…The vertical distribution of Mastigias papua etpisoni throughout the lake is probably related to environmental parameters, which is well recognized in other species (Graham et al 2001) but not fully investigated for Mastigias papua etpisoni . For example, the effects of water temperature, salinity, light and dissolved oxygen on growth, reproduction and survival have been documented for other medusae and polyps (Dong et al 2015, Purcell et al 2012, Suzuki et al 2016). During the REMUS surveys, we measured the distribution of Mastigias papua etpisoni in higher resolution than past studies (Dawson & Hamner 2003, Hamner et al 1982) and found significantly more jellyfish between 6–7 m, where PAR was ~200 umol m −2 s −1 and oxygen was ~2 mg L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide useful insights for future mission planning, validation and analysis that could be used to study jellyfish or other organisms in enclosed or semi-enclosed areas. Ecological concepts, such as habitat choice, diel vertical migration, aggregation structure, predator–prey dynamics and population variability, could be investigated in lagoon, cove and lake systems where jellyfish often live in large populations (Colombo et al 2009, D'ambra et al 2013, Suzuki et al 2016). Therefore, using one platform, behavioural patterns and variability can be examined across many spatiotemporal scales with greater ease and speed compared with traditional methods while also increasing data quantity.…”
Section: Discussionmentioning
confidence: 99%
“…At Kitasato University, the optimal salinity for planula settlement was examined at a temperature of 30 °C and salinity of 3, 5, 10, 15, 20, and 30, which mimicked the salinity range (0-20) in the Perak River estuary [15,16] and in normal seawater (30). A batch of 10…”
Section: Examination Of Suitable Salinity For Planula Settlementmentioning
confidence: 99%
“…At Kitasato University, the optimal salinity for planula settlement was examined at a temperature of 30 • C and salinity of 3, 5, 10, 15, 20, and 30, which mimicked the salinity range (0-20) in the Perak River estuary [15,16] and in normal seawater (30). A batch of 10 planulae 3 days after the fertilization was introduced into one well of a 12-well microplate filled with 5 mL of seawater with each salinity level.…”
Section: Examination Of Suitable Salinity For Planula Settlementmentioning
confidence: 99%